Answer:
g(x) = x+1
Step-by-step explanation:
Informally, you can see that the function h(x) takes the root of a value that is 1 more than the value under the same radical in f(x). This suggests that adding 1 to x in f(x) will give you h(x). That is, ...
h(x) = f(x+1) = f(g(x))
so
g(x) = x+1
_____
More formally, you can apply the inverse of the function f(x) to the equation ...
h(x) = f(g(x))
f^-1(h(x)) = f^-1(f(g(x))) . . . inverse function applied
f^-1(h(x)) = g(x) . . . . . . . . . simplified
Now f^-1(x) can be found by solving for y in ...
x = f(y)
x = ∛(y+2) . . . . . . . . . definition of f(y)
x^3 = y+2 . . . . . . . . . cube both sides
x^3 -2 = y = f^-1(x) . . . subtract 2 from both sides
So, f^-1(h(x)) is ...
f^-1(h(x)) = g(x) = (∛(x+3))^3 -2 = x+3 -2
g(x) = x+1
Annual interest is P*r^t, r is 0.05 here, t is 9/12=3/4=0.75
P*0.05^0.75=120
use your calculaor: P= 120÷ (0.05)^0.75=1135
so he invested about 1135 dollars
<span><span><span><span>
</span>
</span>
</span></span>
A. terminating
b. repeating
c. repeating
d. terminating
e. repeating
i think
We know, Circumference of a Circle = 2πr
C = 2 * 22/7 * 3.5
C = 2 * 22/2
C = 2 * 11
C= 22
In short, Your Answer would be 22 Feet
Hope this helps!